Assessing genotoxic effects of chemotherapy agents by a robust in vitro assay based on mass spectrometric quantification of γ-H2AX in HepG2 cells - Qu, Minmin; Chen, Jia; Xu, Bin; Shi, Qinyun; Zhao, Shujing; Wang, Zhaoxia; Li, Zhi; Ma, Bo; Xu, Hua; Ye, Qinong; Xie, Jianwei (Frontiers in Pharmacology, 2024)
Chemotherapy has already proven widely effective in treating cancer. Chemotherapeutic agents usually include DNA damaging agents and non-DNA damaging agents. Assessing genotoxic effect is significant during chemotherapy drug development, since the ability to attack DNA is the major concern for DNA damaging agents which relates to the therapeutic effect, meanwhile genotoxicity should also be evaluated for chemotherapy agents' safety especially for non-DNA damaging agents. However, currently applicability of in vitro genotoxicity assays is hampered by the fact that genotoxicity results have comparatively high false positive rates. γ-H2AX has been shown to be a bifunctional biomarker reflecting both DNA damage response and repair. Previously, we developed an in vitro genotoxicity assay based on γ-H2AX quantification using mass spectrometry. Here, we employed the assay to quantitatively assess the genotoxic effects of 34 classic chemotherapy agents in HepG2 cells. Results demonstrated that the evaluation of cellular γ-H2AX could be an effective approach to screen and distinguish types of action of different classes of chemotherapy agents. In addition, two crucial indexes of DNA repair kinetic curve, i.e., k (speed of γ-H2AX descending) and t50 (time required for γ-H2AX to drop to half of the maximum value) estimated by our developed online tools were employed to further evaluate 9 representative chemotherapy agents, which showed a close association with therapeutic index or carcinogenic level. The present study demonstrated that mass spectrometric quantification of γ-H2AX may be an appropriate tool to preliminarily evaluate genotoxic effects of chemotherapy agents.